PENGARUH FITUR LIVE SHOPPING TERHADAP PENINGKATAN PENJUALAN DI MARKETPLACE - Mochamad Taufiq Kolil; Ani Nurhayati; Ana Nurhayati (Lembaga Sepercenter, 2025)
Digital transformation has driven significant changes in consumer behavior and marketing strategies in Indonesia's e-commerce sector. One emerging innovation is the Live Shopping feature, an interactive live broadcast that allows sellers to interact directly with buyers. This study aims to analyze the impact of the Live Shopping feature on increasing sales in the marketplace, particularly for Micro, Small, and Medium Enterprises. The approach used was qualitative-descriptive with secondary data obtained from industry reports, academic publications, and official sources such as BPS, Shopee, and iPrice. The results show that Live Shopping has a significant positive impact on transaction volume, customer engagement, and product trust. The findings also show that this feature enables businesses to run more effective promotions at a low cost. However, implementation challenges exist, such as the need for communication skills and technical limitations. Overall, Live Shopping has proven to be an effective and potential digital marketing tool in supporting the growth of MSMEs in the digital economy era.